Application of calcifying bacteria for remediation of stones and cultural heritages - Dhami, Navdeep Kaur; Reddy, M. Sudhakara; Mukherjee, Abhijit (Frontiers in Microbiology, 2014)
Since ages, architects and artists worldwide have focused on usage of durable stones as marble and limestone for construction of beautiful and magnificent historic monuments as European Cathedrals, Roman and Greek temples, Taj Mahal etc. But survival of these irreplaceable cultural and historical assets is in question these days due to their degradation and deterioration caused by number of biotic and abiotic factors. These causative agents have affected not only the aesthetic appearance of these structures, but also lead to deterioration of their strength and durability. The present review emphasizes about different causative agents leading to deterioration and application of microbially induced calcium carbonate precipitation as a novel and potential technology for dealing with these problems. The study also sheds light on benefits of microbial carbonate binders over the traditional agents and future directions.